2013
DOI: 10.2298/pac1301001p
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic characterization of microwave sintered Sr1-xCaxMnO3 (0.0 ≤ x ≤ 0.4) thick films

Abstract: Electromagnetic characteristics of microwave sintered strontium calcium manganites thick film with variation in calcium content have been investigated. The X-ray diffraction analysis reveals tetragonal perovskite structure for all the compositions. The grain size increases with the increase in calcium content. The microwave absorption, complex permittivity, permeability and conductivity are reported in the frequency range of 8.2–18 GHz. The absorption loss is larger in Ku band while insertion loss is larger in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…But in case of Ku band, variation in the values of = is observed as Co concentration increases. The experimental set up and formula for calculating complex permittivity are well explained in the study by Pawar et al, 2013. Figure 6 shows the variation in permittivity loss (Љ) with frequency for (Sr 0.6 Ca 0.4 ) (Co y Mn 1Ϫy ) O 3 (0.2 Յ y Յ 1.0) thick film. From the figure, it is observed that permittivity loss (=) decreases with increase in frequency due to intrinsic electric dipoles and interfacial polarization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But in case of Ku band, variation in the values of = is observed as Co concentration increases. The experimental set up and formula for calculating complex permittivity are well explained in the study by Pawar et al, 2013. Figure 6 shows the variation in permittivity loss (Љ) with frequency for (Sr 0.6 Ca 0.4 ) (Co y Mn 1Ϫy ) O 3 (0.2 Յ y Յ 1.0) thick film. From the figure, it is observed that permittivity loss (=) decreases with increase in frequency due to intrinsic electric dipoles and interfacial polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental set up and formula for calculating complex permittivity and permeability are well explained in Pawar et al (2013). Complex permittivity represents the electronic properties of a material subjected to an electromagnetic field.…”
Section: Resultsmentioning
confidence: 99%